Next steps in supporting people with autistic spectrum conditions - Hatton, Sue; Simpson, John (Los Angeles SAGE, 2012)
This book provides comprehensive information on supporting people with autism and can also be used to achieve the Level 3 unit - Understand how to support individuals with autistic spectrum conditions. If you work with people with autistic spectrum condition and are studying for a health and social care qualification, or you want the right information to help your personal development, then Next steps in supporting people with autistic spectrum condition is for you. This book puts the person with autism at the centre of the support you give. It uses real life stories, activities and thinking points to cover all of the learning outcomes and it is full of practical examples of how to apply the ideas to the support you provide.
"Supporting a unit from the level 3 health and social care qualifications"-Title page.
Includes bibliographical references and index.
Keywords: Autistic people -- Rehabilitation; Autistic people -- Services for; Autism spectrum disorders